Pengaruh Layanan Bimbingan Klasikal dengan Metode Mind Mapping untuk Meningkatkan Literasi Kesehatan Mental pada Siswa - Nathania Azzel, Frecylia Zahra; Rita Sinthia; MT Afriwilda (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2025)
This study aims to determine the effect of classical guidance services with the mind mapping method on students' mental health literacy. This study uses a quantitative approach with a pretest-posttest control group design. The sample consisted of two classes VIII with a total of 60 students selected randomly using the spin wheel application. The instrument was in the form of multiple-choice questions based on three aspects of literacy according to Jorm (2000): knowledge, beliefs, and attitudes. Data were analyzed using the Independent Sample t-test using SPSS version 25. The results showed a significant difference between the gain scores of the two groups (t = 8.059; Sig. 2-tailed = 0.000). This shows that classical guidance services with the mind mapping method are able to improve students' understanding in a more visual, creative, and structured way compared to regular classical services, and provide a positive contribution in shaping students' attitudes towards mental health issues. Keywords: classical guidance, mind mapping, mental health